Overcoming transience and flux: routines in community-governed mass collaborations. Issue 2 (5th June 2017) - Pike, Jacqueline C.; Joyce, Elisabeth W.; Butler, Brian S.
Abstract : Purpose: Community-governed mass collaborations are virtual organizations in which volunteers self-organize to produce content of value. Given the high turnover of participants and the continual development and modification of governance modules, questions arise about how mass collaborations can succeed. Based on organizational routine theory, the purpose of this paper is to investigate how different aspects of routines can support the goals of mass collaborations. Design/methodology/approach: Proposed hypotheses are developed and tested with data from a critical decision-making area of a successful community-governed mass collaboration – Wikipedia's content review process. Findings: The findings support the arguments that routines that reinforce governance serve important roles in enabling mass collaboration in the presence of transient participation and dynamic task demands in addition to creating a greater likelihood of success as outlined by the collaboration. Research limitations/implications: One limitation of this study is that it examines these types of routines in only one context, Wikipedia's content review process, and Wikipedia is an unusually successful, community-governed mass collaboration. However, this can be considered a conservative test as mass collaborations in more formal contexts or in traditional organizations face fewer hurdles due to more stable social norms, routines, and participant populations. Practical implications: Greater understanding of how community-governed mass collaborations "get the work done" in spite of participant transience and governance flux can guide developers in managing flourishing communities. Originality/value: While routines have been studied in traditional organizations, little work has been done with routines in community-governed mass collaborations and how they enable both stability and flexibility.